Aktivitas Pembelajaran Berbasis Proyek Terintegrasi dalam Pendekatan STEM: Pemanfaatan Cardboard bekas dalam Mendesain VR (Virtual Reality) Berdasarkan Konsep Pembiasan Cahaya pada Lensa Cembung Sebagai Media Proyeksi Video 3D untuk Meningkatkan Metaliterasi Siswa - Okti Anis Safiati; Dafik Dafik; Zainur Rasyid Ridlo (jcgant, 2022)
After the Covid-19 pandemic, students are used to online learning, namely learning using gadgets. It is a fact that more students use their gadgets to play online games than educational sites. In playing online games students feel they are in a game that seems real. It's not uncommon for gamers to buy a VR box to play 3D games more realistically. VR or Virtual Reality is a medium of interaction between humans and computers that makes users feel that they are in a computer environment. The aim of this research is to make VR with the right and cheaper materials, namely used cardboard and plastic bottles. The results of this study are Virtual Reality to improve students' metalliteracy abilities. Metalliteration ability is very important in the industrial era 4.0. Metalliteracy is a comprehensive framework of thinking that goes beyond other literacy with the main literacy being technology and information literacy. This metalliteracy ability is still relatively new, therefore, in this study a project-based learning model that is integrated with the STEM (Science, Technology, Engineering, Mathematics) approach is applied to improve students' metalliteracy abilities by presenting STEM problem solving in learning. The STEM problem raised in this study is the use of used cardboard in making VR (virtual reality). Shiva made VR based on the concept of light refraction in convex mirrors, then PjBL and STEM tools were developed in learning to increase student metalliteracy by calculating the surface area of geometric shapes. The results of the research are in the form of learning activities in the form of table descriptions of 1-6 stages of learning activities.